Precursors, the Environment and the West in Seamus Heaney’s “Postscript” - Ross Moore (Estudios Irlandeses, 2018)
Being the final poem in Heaney’s 1996 collection The Spirit Level, situates the poem “Postscript” significantly in Heaney’s poetic oeuvre. The collection was Heaney’s first to be published after winning the Nobel Prize for literature, it was also his first published amidst the changed social and political context following the 1994 paramilitary ceasefires in Northern Ireland. Here, I will explore the manner in which “Postscript” interacts with previous work by Heaney. Looking closely at the language, imagery and procedures of the poem, I argue that the poem embodies a fundamental shift in Heaney’s approach to the natural environment but that this change is reliant on poetic procedures which Heaney had come to trust early in his career. Heaney’s descriptive precision and openness to the “marvellous” combine to produce a uniquely effective poem. “Postscript” treats the natural world and the human subject in a manner atypical of Heaney’s procedures yet stands among his most accomplished work. I will consider the manner in which Heaney’s poem simultaneously exists “post” the “scripts” of literature mythologizing the West of Ireland while remaining in close dialogue with perhaps the most famous of these: Yeats’s poem “The Wild Swans at Coole”.